Competency Development in the Object-oriented Programming Style Education - Muharem Mollov (UIKTEN, 2021)
The article presents a spiral approach for the competency development in the object-oriented programming style education as a part of the occupation “Application programmer” of the national program “Education for IT career” (NPEITC) in the Bulgarian Ministry of Education and Science. The education is realized by a system of tasks comprising topically linked modules of the study plan. Such system is demonstrated and the obtained results from its application, followed by the analyses confirm the success of the competency approach, are presented.